Educational Robotics and Tangible Devices for Promoting Computational Thinking - Funk, Matthias G.; Cascalho, Jose Manuel; Santos, Ana Isabel; Mendes, Armando B. (Frontiers in Robotics and AI, 2021)
Recently, efforts have been made to add programming activities to the curriculum that promote computational thinking and foster 21st-century digital skills. One of the programming modalities is the use of Tangible Programming Languages (TPL), used in activities with 4+ years old children. In this review, we analyse solutions proposed for TPL in different contexts crossing them with non-TPL solutions, like Graphical Programming Languages (GPL). We start to characterise features of languages interaction, their use, and what learning activities are associated with them. Then, in a diagram, we show a relation between the complexity of the languages with factors such as target age and output device types. We provide an analysis considering the type of input (e.g. TPL versus GPL ) and output devices (e.g. physical robot versus graphical simulation) and evaluate their contribution to further insights about the general trends with respect to educational robotic systems. Finally, we discuss the opportunities to extend and improve TPLs based on the different solutions identified.